Modeling and Implementing Record Linkage in Health Information Systems - Philip, Achimugu; Abimbola, Soriyan; Babajide, Afolabi (The Journal on Information Technology in Healthcare, 2020)
The Journal on Information Technology in Healthcare,Volume 7, No 3, p.169–181.